Profil Penggunaan Obat dalam Swamedikasi pada Ibu-Ibu PKK di Kecamatan Garut Kota - Genialita Fadhilla; Siva Hamdani (STIKes Karsa Husada Garut, 2021)
Self-medication is an independent treatment that carried out to deal with minor complaints by only using over-the-counter drugs that are limited. Self-medication is commonly used by the mothers to treat their families when they suffering from pain. If self-medication done properly, it can be a big contribution to the government, especially to maintaining national health. However, self-medication will be at risk if the treatment is done incorrectly. The study was conducted using a descriptive observational study method by giving a posttest questionnaire and pretest to assess medicine use and habits in self-medication to 50 PKK mothers in Garut sub-district, Garut Regency. The results of the study showed that the highest number of self-medication was fever and ulcer (26%), the type of drug that they used was modern medicine (70%), the choice of drugs used were antipyretic analgesic drugs (44%). Wilcoxon test indicates that there is a significant influence after giving counseling to the choice of habitual answers in self-medication for respondent (p<0.05).